2005
DOI: 10.1534/genetics.104.040048
|View full text |Cite
|
Sign up to set email alerts
|

The dst1 Gene Involved in Mushroom Photomorphogenesis of Coprinus cinereus Encodes a Putative Photoreceptor for Blue Light

Abstract: The homobasidiomycete Coprinus cinereus exhibits remarkable photomorphogenesis during fruiting-body development. Under proper light conditions, fruiting-body primordia proceed to the maturation phase in which basidia in the pileus undergo meiosis, producing sexual spores, followed by stipe elongation and pileus expansion for efficient dispersal of the spores. In the continuous darkness, however, the primordia do not proceed to the maturation phase but are etiolated: the pileus and stipe tissues at the upper pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(133 citation statements)
references
References 42 publications
6
125
0
2
Order By: Relevance
“…Genes similar to WC1 have also been reported in L. edodes (PHRA; Sano et al, 2008) and in C. cinerea (dst1; Terashima et al, 2005). The C. cinerea dst1 mutant cannot form a mature cap under normal light/dark conditions, and the shape of the fruiting body of the dst1 mutant is very similar to that formed by the wild-type mushroom when grown in complete darkness (Terashima et al, 2005). Since WC2 and PHRA in L. edodes interact with each other, they could act as a blue light receptor in L. edodes that regulates fruiting body development in the light (Sano et al, 2010).…”
Section: Wwwintechopencommentioning
confidence: 75%
See 1 more Smart Citation
“…Genes similar to WC1 have also been reported in L. edodes (PHRA; Sano et al, 2008) and in C. cinerea (dst1; Terashima et al, 2005). The C. cinerea dst1 mutant cannot form a mature cap under normal light/dark conditions, and the shape of the fruiting body of the dst1 mutant is very similar to that formed by the wild-type mushroom when grown in complete darkness (Terashima et al, 2005). Since WC2 and PHRA in L. edodes interact with each other, they could act as a blue light receptor in L. edodes that regulates fruiting body development in the light (Sano et al, 2010).…”
Section: Wwwintechopencommentioning
confidence: 75%
“…WC2 in L. edodes was cloned and characterized; the protein has been designated PHRB; Sano et al, 2009). Genes similar to WC1 have also been reported in L. edodes (PHRA; Sano et al, 2008) and in C. cinerea (dst1; Terashima et al, 2005). The C. cinerea dst1 mutant cannot form a mature cap under normal light/dark conditions, and the shape of the fruiting body of the dst1 mutant is very similar to that formed by the wild-type mushroom when grown in complete darkness (Terashima et al, 2005).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Onset of expression of two genes encoding fruiting body specific galectins (b-galactoside sugarbinding lectins) correlates with the formation of primary and secondary hyphal knots, respectively, and continues during primordia development (Boulianne et al 2000;Bertossa et al 2004). In addition, four genes have been identified that act in cap and stipe tissue formation and stipe elongation, respectively, including one for a potential photoreceptor Kamada 1998, 2000;Arima et al 2004;Terashima et al 2005). Next to the gene described in this study, a yet uncharacterized gene acting in fruiting body initiation has also been cloned (Clergeot et al 2003).…”
Section: T He Heterothallic Fungus Coprinopsis Cinerea Servesmentioning
confidence: 97%
“…The WC-2 protein contains a zinc-finger and 1 PAS domain (17), and interacts with WC-1 to form a complex that binds to the promoters of light-inducible genes, presumably to activate their transcription (13,18,19). WC proteins are required for the responses to blue light in the basidiomycete fungi Cryptococcus neoformans (20,21) and Coprinus cinereus (22), and 3 wc-1 genes have been described in the zygomycetes Rhizopus oryzae and Mucor circinelloides (23,24). A Mucor WC-1 protein is modified by ubiquitylation, presumably to regulate its activity (25).…”
mentioning
confidence: 99%